Legal Aspects in The Process of Damages in Civil Courts - Gerardus Gegen (LEGAL BRIEF, 2021)
The development of national development must first be centered on the development of equitable human resources, therefore in an effort to fulfill this, the Indonesian government wants to strive to form an Indonesian society that is skilled, honest and prosperous, one aspect that is currently being targeted by the central government is the aspect of Indonesian legal policy. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the legal system in Indonesia consists of several categories, the first is criminal law, the second is civil law, and the third is national customary law. each of these laws has different characteristics and regulations, there is one law that specifically regulates the system of compensation, disputes, and disputes in court, after a court decision comes out, it is not uncommon for new conflicts to arise and make policies new to an agreement that is not in line with expectations, these actions are called default and unlawful acts, the two legal processes were born because of a compensation that must be carried out by both parties in completing various remaining legal processes.